2018
DOI: 10.1002/adma.201707382
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteric Liquid Crystal Shells as Enabling Material for Information‐Rich Design and Architecture

Abstract: The responsive and dynamic character of liquid crystals (LCs), arising from their ability to self-organize into long-range ordered structures while maintaining fluidity, has given them a role as key enabling materials in the information technology that surrounds us today. Ongoing research hints at future LC-based technologies of entirely different types, for instance by taking advantage of the peculiar behavior of cholesteric liquid crystals (CLCs) subject to curvature. Spherical shells of CLC reflect light om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
131
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 105 publications
(140 citation statements)
references
References 61 publications
2
131
0
Order By: Relevance
“…As color is one of the most natural indicators seen by the naked eye, the mechanochromic response of CLCEs is attractive far beyond lasing. CLCEs could enable tensile and/or pressure sensors capable of visualizing mechanical strain in many objects of significant societal, technical, and/or commercial importance, such as clothing, packaging, pressurized vessels or in various architectural features . Picot et al demonstrated such a strain sensor operating in real‐time, albeit with an optical response range no greater than ≈40 nm (from orange to green); this limitation can be traced back to the bilayer nature of the sensor, the cholesteric being supported on a nylon substrate that restrains the overall elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…As color is one of the most natural indicators seen by the naked eye, the mechanochromic response of CLCEs is attractive far beyond lasing. CLCEs could enable tensile and/or pressure sensors capable of visualizing mechanical strain in many objects of significant societal, technical, and/or commercial importance, such as clothing, packaging, pressurized vessels or in various architectural features . Picot et al demonstrated such a strain sensor operating in real‐time, albeit with an optical response range no greater than ≈40 nm (from orange to green); this limitation can be traced back to the bilayer nature of the sensor, the cholesteric being supported on a nylon substrate that restrains the overall elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [ 38 ] Copyright 2018, Wiley‐VCH. d) The optical signature of planar‐aligned ChLC shells and the schematic drawing of the reflection behavior.…”
Section: Synthesis Structure and Properties Of Structural Color Matmentioning
confidence: 99%
“…The intrinsically random textures of the cholesteric phase, generated from nonequilibrium states of the liquid crystals under quick solidifying, have been used for unpredictable identifier tags for enhanced security. [ 38 ] The great diversity of optical features enable physically unique and unclonable encryption means. Moreover, various optical images could be generated from a single cholesteric liquid crystal.…”
Section: Synthesis Structure and Properties Of Structural Color Matmentioning
confidence: 99%
See 2 more Smart Citations